Pengembangan Media Pembelajaran Big Book untuk Pembentukan Karakter Anak Usia Dini - Kiromi, Ivonne Hafidlatil (LP3M Universitas Islam Zainul Hasan Genggong, 2017)
This study aims to assist teachers in developing instructional media particularlyinstructional media in shaping the character of young children in early childhoodBakti Baitus salam Bantul. This study uses research and development (R&D).The media that has been resulted is the big book media. Data obtainedthrough interview techniques, expert assessment sheet soft media and materials.This research subject is child play group stotaling 28 children. Based on theresults of the data analysis and discussion, it can be concluded that learningmedia can be assist teachers in developing instructional media particularlyinstructional media in shaping the character of young children.The resultsshow that use big book positively effect on the child character building, theexperimental class is to gain a higher score is 43 and the control class to obtaina score of 39,14.